Relatedness Among Three Native Geese in Erbil Governorate Using Hematological and Molecular Methods - A. Ahmed, Mohsen; Al-Barzinji, Yousif M.S.; Assad Ismail, Lanja (Kurdistan Journal of Applied Research, 2019)
The objective of the present study was to determine genetic diversity among three geese color types using RAPD markers and hematological parameters. The overall mean, of the live weights, Hemoglobin, Hetrophil %, Lymphocyte %, Monocyte %, and H/L ratio were 3.006 (kg), 14.64, 36.896, 49.896, 2.233 and 0.736 respectively. The breed, sex and interaction between them have a significant effect on live body weight, Hemoglobin, and Monocyte %. Ten primers were used and six out of them were selected based on their number of bands (NB) and polymorphic characteristics. A total of 309 bands observed, ranged from 30 in primer OPB-07 to 54 bands in OPA-20. Five unique bands were found only in white goose, whereas the highest unique band was obtained in primer OPB-01 locus. Overall genetic distance among native geese arrived 64.122 and phylogenetic dendrograms showed that 3 clusters, the first cluster content only white geese (Male and Female) breed, the second one cluster is included piebald geese breed (Male and female) and the third one was including gray geese (Male and female) breed. It was concluded that the white geese was closer to piebald geese than to the gray geese breed. The high genetic distance (64.122%) and variation in phenotypic value such as live weight (2.375 to 3.600 kg/bird) for three native geese indicate that these native geese have a good amount of genetic resources to made genetically improvement in further and it means the three goose samples are independent breeds.